À la recherche des « voix » des fallāhīn dans un dossier d’archives judiciaires égyptiennes - Anne Clément (Ateliers d'Anthropologie)
Through the study of the legal file of Mikhīmar (a young fallāh or Egyptian peasant sentenced to death for murder in 1893), this article shows that an approach to the archives focusing on the material traces left by the process of composing and recomposing the file makes it possible to partially reconstruct the performance of the different actors of the legal process, and thereby helps to shed a new light on the colonial justice system at the turn of the 20th century. More precisely, the analysis of the traces—quotations between brackets and petitions in appendices—left by the negotiation that unfolded throughout the procedure between the victim’s family and the legal authorities over the nature of the crime as a proxy murder and the action to be taken against those responsible, reveals both the conflictual and highly political dimension of the legal professionals’ decision-making process and an unsuspected ability on the part of the fallāhīn to express themselves and challenge the system.